Effects of topological disorder in unsaturated granular media via a pore-scale lattice Boltzmann investigation. (March 2021) - Shi, Zhang; Wang, Zhongzheng; Gan, Yixiang
Highlights: We studied combined effects of topological disorder and wettability on multi-phase flow in wet granular media using pore-scale lattice Boltzmann simulations. The increasing topological disorder can enhance the connectivity of liquid clusters, leading to a larger mean cluster volume and an early transition towards the funicular state from pendular state. Correlations between the proposed capillary index, capturing effects from both topological disorder and wettability, and water retention curves are identified. Abstract: In this study, we investigate the impact of topological disorder on liquid distribution and transport phenomena in three-dimensional unsaturated granular media using the Shan-Chen lattice Boltzmann method. Distinct samples of disordered media are generated, characterized by the disorder index I v . Under different I v, varied liquid cluster distributions are demonstrated in a gravity-driven vapour-liquid system. Gradually increasing the initial liquid phase in the simulation domain allows the full range of saturation. The focuses are placed on the liquid cluster statistics from the connectivity, total cluster number, largest cluster and mean cluster volume at an increasing saturation. Meanwhile, the interfacial area, liquid retention curves and relative permeability-saturation curves are produced at diverse I v and wettability. It is found that the slopes of retention curves are well correlated with the proposed capillary index I c that unifies both disorder and wettability. The proposed generalized correlation between capillary index and slope index is useful in terms of determining the capillary pressure-saturation curve and relative permeability-saturation curve for a given granular system at varied contact angles. Additionally, the cohesive strength-saturation curves are also obtained with the aid of the interfacial area and negative capillary pressure, which elucidates that a packing with a higher I v experiences a relatively larger cohesive strength. These results enhance the understanding of disorder effect and will be beneficial for the exploration of many retention curves-related phenomena such as liquid transfer and stress-strain relation for wet granular media.